2011
DOI: 10.1203/pdr.0b013e3182114ec9
|View full text |Cite
|
Sign up to set email alerts
|

Motherʼs Milk-Induced Hsp70 Expression Preserves Intestinal Epithelial Barrier Function in an Immature Rat Pup Model

Abstract: Preterm infants face many challenges in transitioning from the in utero to extrauterine environment while still immature. Failure of the preterm gut to successfully mature to accommodate bacteria and food substrate leads to significant morbidity such as neonatal necrotizing enterocolitis. The intestinal epithelial barrier plays a critical role in gut protection. Heat shock protein 70 (Hsp70) is an inducible cytoprotective molecule shown to protect the intestinal epithelium in adult models. To investigate the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 44 publications
3
43
0
1
Order By: Relevance
“…In the current study, Trichinella spiralis infection reduced ileal ZO1 and occludin1 abundances, which may contribute to the alteration in intestinal permeability. Liedel et al reported that mother's milk-induced HSP70 expression preserves intestinal epithelial barrier function in an immature rat pup model (Liedel et al 2011), which is similar with our results that preinduction of HSP70 significantly reversed the intestinal dysfunction caused by Trichinella spiralis infection. There are also a large number of studies demonstrating a protective role of HSP70 in intestinal barrier, including ischemiareperfusion (I/R) mucosal injury (Fleming et al 2002), ethanol-induced intestinal damage (Lee et al 2014a), and chronic water avoid stress (Yang et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, Trichinella spiralis infection reduced ileal ZO1 and occludin1 abundances, which may contribute to the alteration in intestinal permeability. Liedel et al reported that mother's milk-induced HSP70 expression preserves intestinal epithelial barrier function in an immature rat pup model (Liedel et al 2011), which is similar with our results that preinduction of HSP70 significantly reversed the intestinal dysfunction caused by Trichinella spiralis infection. There are also a large number of studies demonstrating a protective role of HSP70 in intestinal barrier, including ischemiareperfusion (I/R) mucosal injury (Fleming et al 2002), ethanol-induced intestinal damage (Lee et al 2014a), and chronic water avoid stress (Yang et al 2009).…”
Section: Discussionsupporting
confidence: 92%
“…54 Conversely, decreased intestinal HSP70 and leaky intestine were reported in a model of necrotic enterocolitis in rats. 55 In summary, iHSPs have many vital cellular functions. Expression of iHSPs is modulated by inflammatory and oxidative stress and is involved in major cellular physiological functions of GECs.…”
Section: Gut Barrier Functionmentioning
confidence: 99%
“…89 In a rat model of necrotizing enterocolitis induced by maternal separation and milk formula feeding, the expression of both ileal iHSP70 protein and gene was reduced. 55 Mother's milk was hypothesized to induce physiological levels of iHSP70 in normal rat pups, though precise mechanisms were not disclosed. 55 Another group confirmed reduced intestinal iHSP70 in both human and mouse necrotizing enterocolitis.…”
Section: Inducible Heat-shock Proteins and Gastrointestinal Diseases mentioning
confidence: 99%
See 2 more Smart Citations